Total Elbow Arthroplasty as the Treatment of Choice for a Young Man with Neglected Terrible Triad of the Elbow Joint and Schizophrenia: A Case Report - Savio SD; Artha KYW; Wiguna IGLNAA (Malaysian Orthopaedic Journal)
In young patients, the use of total elbow arthroplasty (TEA) is rarely preferred due to its high rate of mechanical failure. Poor compliance and psychological problems encountered may lead to increased difficulty in management. A 38-year-old male complained stiffness and pain on his left elbow. History of trauma was present 10 months ago, when he fell down from a tree of 6m high. Immediate closed reduction and immobilisation with backslab was performed, but he was lost to follow-up due to Schizophrenia. In physical examination, we found varus and recurvatum deformity with inability to flex the elbow beyond 30° and perform pronation. Plain radiograph and CT scan confirmed the terrible triad of elbow with callus formation. Total elbow arthroplasty with soft tissue release was then performed, resulting in satisfactory range of motion at one year follow-up. The management of neglected terrible triad of the elbow is challenging not only due to the bony problems, but also contracted muscles and fibrotic joint. TEA previously has been described in cases of inflammatory arthritis and degenerative arthritis, less in post-traumatic conditions especially in young patients. Though there is still scarcity in literatures discussing the burden of psychiatric problems in arthroplasty patients, but the existing literatures proved the correlation between psychiatric comorbidity with higher rate of post-operative adverse events. Total elbow arthroplasty can be considered as a surgical treatment for a young patient with neglected fracture dislocation of elbow with satisfactory result; however close post-operative monitoring and routine physiotherapy exercise should always be performed.